Seismic velocity structure under Lembang Fault, West Java, Indonesia: The first result of Lembang fault Integrated gps-seismic observatory Network, a collaborative research between National Agency for Research and Innovation of Indonesia and Earth Observatory of Singapore - Hidayat, Dannie (2023)
Lembang Fault is one the major fault in the Western region of Java, Indonesia, located just 10-15 km north of Bandung (capital city of West-Java). Although this fault has little to no significant historical of big earthquake records, the fault shows significant geomorphic evidence of its tectonic activity. Previous study of this geomorphic markers combine with paleoseismological trenching data and the geodetic study based on GPS campaign method suggest that this 29 km length- fault has a dominantly sinistral sense of movement with relatively very low slip rate. Even if the rate is small, the fault could potentially generate a M6.5 to M7 earthquake, strong and considerably very damaging to nearby Bandung city populous area. Starting April 2022, the National Agency for Research and Innovation (BRIN) of Indonesia and Earth Observatory of Singapore (EOS) collaboratively install four continuous seismo-geodetic stations in the vicinity of Lembang Fault to monitor seismic activity and active fault movement of the Lembang Fault and to get movement information when the Lembang Fault earthquake occurs. The collaboration also aimed to strengthen data-based and geoscience-based Earthquake Disaster Risk Reduction efforts, and become a model observatory that bridges from earth science to local government policies and complete public education from upstream to downstream. In the first several months since the installation, we have collected seismic data from teleseismic earthquakes recorded by our stations as well as a few other seismic stations around Lembang Fault. Waveforms from the earthquakes recorded have been analysed, we performed a joint inversion of teleseismic receiver functions and surface waves (H/V ratio). The preliminary results, based on the forward and the inversion method of receiver function, suggest the crustal thickness underneath the station is about 25-30 km. In addition, there are some variability in back azimuth 90-180 degree which may be caused by waves traveling through the nearby active volcano.